Intrinsic Preferences for Autonomy - Jana Freundt; Holger Herz; Leander Kopp (Center for Economic Studies and ifo Institute (CESifo), 2023)
Personal autonomy has been argued to be fundamental to well-being and is often discussed as an important driver of economic and political behavior. Yet, preferences for autonomy are not well understood, because their identification requires the separation of instrumental value attached to autonomous choice. We propose a novel elicitation method that solves this identification challenge. We establish the existence of intrinsic preferences for choice autonomy and show substantial heterogeneity in a large online sample. We further study their antecedents by relating them to existing personality scales and socioeconomic characteristics. Finally, we test their association with other preferences, attitudes and beliefs.
Keywords: D01; D90; C91; 330; autonomy; preference measurement; experiment